Psychological distress and wellbeing as mediators between anti-mattering (feelings of insignificance) and irritability among Lebanese adolescents: A cross-sectional study - Michelle Abi Karam; Rabih Hallit; Diana Malaeb; Fouad Sakr; Mariam Dabbous; Feten Fekih-Romdhane; Sahar Obeid; Souheil Hallit (PLoS ONE, 2025)
Background This study examined the mediating effect of psychological distress and wellbeing in the association between anti-mattering and irritability among a sample of Lebanese adolescents—a topic that remains largely underexplored in adolescent mental health research. Methods A cross-sectional study was conducted during November 2023 and included 763 adolescents currently residing in Lebanon (mean age 16.08 ± 1.74 years, 37.6% males and 62.4% females) recruited from all Lebanese governorates using a snowball sampling technique. Data were collected via an online questionnaire and analyzed using the PROCESS Macro for mediation analysis. Results The findings indicated that both psychological distress (β = .39, BootSE = .04, 95% CI [.33,.46]) and wellbeing (β = .07, BootSE = .02, 95% CI [.03,.12]) partially mediated the relationship between anti-mattering and irritability. Adolescents with higher levels of anti-mattering reported greater distress and reduced wellbeing, both of which were associated with increased irritability. Conclusion Our results highlight the psychological relevance of anti-mattering in adolescence and suggest that addressing feelings of insignificance may play a key role in managing emotional dysregulation. Mental health practitioners and educators should consider developing culturally sensitive interventions that target feelings of anti-mattering, enhance wellbeing, and reduce psychological distress. School-based programs promoting emotional support and social inclusion may prove especially beneficial. Future studies should investigate these associations longitudinally and across varied cultural contexts to better inform prevention and intervention strategies.